A Systematic Review of Transcranial Direct Current Stimulation in Primary Progressive Aphasia: Methodological Considerations - Coemans, Silke; Struys, Esli; Vandenborre, Dorien; Wilssens, Ineke; Engelborghs, Sebastiaan; Paquier, Philippe; Tsapkini, Kyrana; Keulen, Stefanie (Frontiers in Aging Neuroscience, 2021)
A variety of tDCS approaches has been used to investigate the potential of tDCS to improve language outcomes, or slow down the decay of language competences caused by Primary Progressive Aphasia (PPA). The employed stimulation protocols and study designs in PPA are generally speaking similar to those deployed in post-stroke aphasic populations. These two etiologies of aphasia however differ substantially in their pathophysiology, and for both conditions the optimal stimulation paradigm still needs to be established. A systematic review was done and after applying inclusion and exclusion criteria, 15 articles were analysed focusing on differences and similarities across studies especially focusing on PPA patient characteristics (age, PPA variant, language background), tDCS stimulation protocols (intensity, frequency, combined therapy, electrode configuration) and study design as recent reviews and group outcomes for individual studies suggest tDCS is an effective tool to improve language outcomes, while methodological approach and patient characteristics are mentioned as moderators that may influence treatment effects. Special attention is paid to the importance of a language background assessment as well as the considerations to take into account in case of bilingual PPA patients, something that has been overlooked in current tDCS research. Furthermore, we put forward a new perspective on a possible electrode configuration to be considered: stimulation of the cerebellum, an area fairly spared in terms of neurodegeneration in the early stages of PPA.